Robust intervention for oxidative stress-induced injury in periodontitis via controllably released nanoparticles that regulate the ROS-PINK1-Parkin pathway - Li, Xincong; Zhao, Yue; Peng, Haoran; Gu, Deao; Liu, Chao; Ren, Shuangshuang; Miao, Leiying (Frontiers in Bioengineering and Biotechnology, 2022)
Oxidative stress in periodontitis has emerged as one of the greatest barriers to periodontal tissue restoration. In this study, we synthesized controlled drug release nanoparticles (MitoQ@PssL NPs) by encasing mitoquinone (MitoQ; an autophagy enhancer) into tailor-made reactive oxygen species (ROS)-cleavable amphiphilic polymer nanoparticles (PssL NPs) to regulate the periodontitis microenvironment. Once exposed to ROS, which were substantially overproduced under oxidative stress conditions, the ROS-cleavable PssL was disintegrated, promoting the release of the encapsulated MitoQ. The released MitoQ efficiently induced mitophagy through the PINK1-Parkin pathway and successfully reduced oxidative stress by decreasing the amount of ROS. With the gradual decrease in the ROS level, which was insufficient to disintegrate PssL, the release of MitoQ was reduced and eventually eliminated, which contributed to a redox homeostasis condition and facilitated the regeneration of periodontal tissue. MitoQ@PssL NPs have great potential in the treatment of periodontitis via microenvironment-controlled drug release, which will provide a new avenue for periodontal regeneration and diseases related to imbalanced redox metabolism.